Identifying the Weights in Exchange Market Pressure - Franc Klaassen (Tinbergen Institute, 2011)
Exchange market pressure (EMP) measures the pressure on a currencyto depreciate. It adds to the actual depreciation a weightedcombination of policy instruments used to ward off depreciation,such as interest rates and foreign exchange interventions, where theweights are their effectiveness. The key difficulty in the literature ishow to identify these weights. We exploit the persistence of pressureand add instruments based on currency crisis theories to identify theweights, and we propose a simple IV regression to estimate them.An application to the European Monetary System crisis in 1992-1993shows that a one percentage point higher interest rate wards off adepreciation of about 0.2 percent.
Keywords: C26; E42; E58; F31; F33; 330; currency crisis models; ERM crisis; exchange rate regime; instrumental variables; monetary policy; persistence; Kapitaleinkommen; Prognoseverfahren; ARCH-Modell; Bayes-Statistik; Modellierung; Theorie